HUBUNGAN PENGETAHUAN, SARANA PRASARANA, DAN PENGAWASAN DENGAN PERILAKU PENERAPAN SOP PEKERJA CONFINED SPACE - Ratih Putri Ramadhani (The Indonesian Journal of Occupational Safety and Health, 2018)
Working in confined space has very high risks, therefore, one of the hierarchy control to manage identified risk is administrative by implementing Standard Operating Procedures (SOP). The implementation of SOP correlates with the worker behaviors. The purpose of this research is to find out correlation between knowledge, facilities, and supervision to implementation behaviors of sop in confined space. This study is an observational descriptive research using cross sectional approach. The subject is a total population of 19 cleaning workers in Ducting Dust Collector PT. X . The data provided in distribution of frequency tables and was analyzed using crosstabulation followed with Phi and Cramers V Coefficient to see the relation strength. The result of the study shows that most of the workers has a good behavior in implementing the working SOP in  confined space. According to Phi and CramersV Coefficient, Knowledge (0,57) and Facilities (0,57) has a strong relation with the implementation behavior of SOP in confined space. Supervision has no relationship at all with the implementation behavior of working SOP within the confined space. Keywords: confined space, behavior, SOP